Income diversification and profit efficiency of Chinese banks - Li, Huayi (2022)
This paper examines the impact of income diversification on profit efficiency of banks by using a sample of 112 commercial banks from China during the period of 2015-2020. This paper used a modified Herfindahl-Hirschman Index (HHI) to examine bank’s income diversification and the stochastic frontier approach (SFA) is used to measure profit efficiency. Then the relationship between diversification and bank efficiency is examined by fixed-effects panel regressions. The results indicate that Chinese banks with more income diversification are associated with lower profit efficiency.